Adherence to therapeutic recommendation in relapsing-remitting multiple sclerosis patients - Chojdak-Łukasiewicz, Justyna; Kołtuniuk, Aleksandra; Sawicka, Ewa; Pokryszko-Dragan, Anna (Frontiers in Immunology, 2025)
BackgroundAdherence to disease-modifying therapies (DMTs) in multiple sclerosis (MS) is crucial for effective treatment. Understanding the patients’ perspective and identification of factors influencing adherence to treatment may allow improved disease management.ObjectiveThis study attempted to evaluate adherence to DMTs in people with MS and explore potential patient-related factors influencing level of adherence.Methods121 patients with relapsing-remitting MS (90% women, aged 34.0 ± 10 years participated in the online self-reported survey, which included: Adherence in Chronic Diseases scale (ACDS), Patient health questionnaire (PHQ-9) as a measure of depression, Modified Fatigue Impact Scale (MFSI), Perceived Stress Scale (PSS-10), Acceptance of Illness Scale (AIS), and a questionnaire about demographics and basic patient-reported clinical data.ResultsThe ACDS results comprised between 9 and 28 points, with a mean value of 24.0 ± 3.8, indicating a moderate level of adherence. Fatigue was reported by 70% of patients and the results of MFIS showed significant correlation with ACDS (R=-0.260; p=0.004) and AIS score (R=0.487; p <0.001). Relationships were found between the results of AIS and PHQ-9 and PSS-10 but none of them was associated with ACDS, and neither were demographic data.ConclusionsThe adherence to treatment among MS patients is moderate and significantly associated with fatigue. Evaluating the level of adherence and the patients’ psychosocial condition may contribute to personalized and optimal therapeutic approach.